Application of Special Cross-midline Blood Supply Internal Mammary Artery Perforator Flap for Facial Reconstruction - Yinghong Su, MD; Wenzheng Xia, MD, PhD; Haizhou Li, MD; Xin Huang, MD, PhD; Yingfei Sun, MD; Yashan Gao, MD, PhD; Tao Zan, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Severe burn injuries may limit head and neck mobility while distorting facial features; they also place significant psychological strain on patients. The anterior thoracic area, similar in color and texture to the adjacent face–neck regions, often uses preexpanded flaps for reconstruction. Preexpanded internal mammary artery perforator (IMAP) flaps can further minimize donor area damage, provide a relatively thin flap for repairing large skin defects, and do not require an additional graft flap to close the donor site. In this article, we presented a case involving prolonged tissue expansion leading to an atypical vascular supply pattern within the patient’s flap. The compression of ipsilateral vessels promoted a reconfiguration of choke vessels in the trans-perforasome zones, transforming them into functional vessels that serve as primary perforators for the preexpanded IMAP flap. This case validates and extends applications of perforasome theory within clinical settings. The perforasome is a 3-dimensional anatomical unit that comprises a single perforator vessel interconnected with adjacent perforators via either a true or choke vessel. These remodeled vessels subsequently served as the dominant perforator supplying the preexpanded IMAP flap. It also suggests that in instances of excessive expansion, the flap experienced ischemia and hypoxia, exhibiting a vascular remodeling process similar to “delayed” flaps. Therefore, this can be actively leveraged to execute intricate surgical procedures.